Comparative Analysis of the Gut Microbial Communities in Forest and Alpine Musk Deer Using High-Throughput Sequencing - Hu, Xiaolong; Liu, Gang; Shafer, Aaron B. A.; Wei, Yuting; Zhou, Juntong; Lin, Shaobi; Wu, Haibin; Zhou, Mi; Hu, Defu; Liu, Shuqiang (Frontiers in Microbiology, 2017)
The gut ecosystem is characterized by dynamic and reciprocal interactions between the host and bacteria. Although characterizing microbiota for herbivores has become recognized as important tool for gauging species health, no study to date has investigated the bacterial communities and evaluated the age-related bacterial dynamics of musk deer. Moreover, gastrointestinal diseases have been hypothesized to be a limiting factor of population growth in captive musk deer. Here, high-throughput sequencing of the bacterial 16S rRNA gene was used to profile the fecal bacterial communities in juvenile and adult alpine and forest musk deer. The two musk deer species harbored similar bacterial communities at the phylum level, whereas the key genera for the two species were distinct. The bacterial communities were dominated by Firmicutes and Bacteroidetes, with the bacterial diversity being higher in forest musk deer. The Firmicutes to Bacteroidetes ratio also increased from juvenile to adult, while the bacterial diversity, within-group and between-group similarity, all increased with age. This work serves as the first sequence-based analysis of variation in bacterial communities within and between musk deer species, and demonstrates how the gut microbial community dynamics vary among closely related species and shift with age. As gastrointestinal diseases have been observed in captive populations, this study provides valuable data that might benefit captive management and future reintroduction programs.